BRO501: Broadcast production / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2017)
This course is offer as a professional course subject for the third semester students. It encourages students to use their creativity to produce TV programs. They will also experience how a production crew works and managed in the studio and on the field.